2018
DOI: 10.1590/1981-52712015v42n2rb20170027
|View full text |Cite
|
Sign up to set email alerts
|

A Percepção dos Estudantes de Medicina sobre a Influência do Mediarte na Educação Médica

Abstract: RESUMO O brincar é uma ferramenta de extrema importância para todas as crianças e, no hospital, representa uma fuga do ambiente desgastante e dos sintomas da doença. Nesse contexto, o Mediarte: com Amor e Humor é um projeto de extensão que visa à prática da ludoterapia, musicoterapia e palhaçoterapia, no setor de Pediatria do hospital universitário e que, além de transformar a vida das crianças, acredita-se ter potencial para influenciar os voluntários – estudantes de Medicina do curso da Universidade Federal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(23 reference statements)
0
4
0
3
Order By: Relevance
“…The difficulties in dealing with certain patients and even the fact that some of them do not enjoy art activities in hospitals have been reported in other studies in Brazil 41 . In a study on the performance of clowns in a hospital in Minas Gerais, patients reported that accepting the visit of a clown depends a lot on their emotional state and the moment they are going through 42 .…”
Section: Thematic Dimension Of Dancementioning
confidence: 60%
“…The difficulties in dealing with certain patients and even the fact that some of them do not enjoy art activities in hospitals have been reported in other studies in Brazil 41 . In a study on the performance of clowns in a hospital in Minas Gerais, patients reported that accepting the visit of a clown depends a lot on their emotional state and the moment they are going through 42 .…”
Section: Thematic Dimension Of Dancementioning
confidence: 60%
“…Additionally, tests for entering the extension programs were also mentioned as a demotivating factor. Amorim and Bedaque 10 stated that students could be motivated to participate in activities that only require the demonstration of will and responsibility through a letter of interest.…”
Section: Discussionmentioning
confidence: 99%
“…This study reiterates that medical students are motivated to participate in CBEA as this experience adds to their credits and leads to improvement in the curriculum. 1,3,[8][9][10][11][12] Students also expressed that their desire to help society is a motivating factor to participate in these activities. It is noteworthy that the desire to help people is the reason that many students choose medicine as a profession.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os resultados apontam para a melhora da ansiedade dos pacientes e acompanhantes, bem como para maior bemestar da equipe de profissionais 10 . Outra perspectiva explorada é sobre o impacto do treinamento de palhaço e técnicas teatrais para estudantes da área da saúde como uma forma de desenvolver competências interpessoais e humanistas, tais como empatia, comunicação verbal e não verbal, escuta ativa e autoconhecimento 2,[11][12][13][14]…”
Section: Introductionunclassified